PREPARATION AND CHARACTERISATION OF SOAPS USING FIVE DIFFERENT TYPES OF OIL - NSI, E.W.; EKANEM, E. O. (Academy Journal of Science and Engineering)
Bar soaps were prepared using different types of oils. The oils used were palm oil, palm kernel oil, groundnut oil, olive oil and beef tallow. Quality analysis of the soap prepared was carried out and the result was compared with the standard specification for hard soap. The results indicate total fatty matter (T.F.M.) to be 68%, 64%, 54%, 60%, and 58% for palm kernel oil, palm oil, beef tallow, groundnut oil and olive oil respectively. Results of the analysis also indicate ranges of values for other properties such as total free alkali; T.F.A (0.134 – 0.171)%, free caustic alkali, FCA, (0.126 – 0.165)%, free carbonate alkali, F.Ca.A. (0.003 – 0.009)%, lather volume (150 – 440) cm3, time for foam to subside (11.1 – 23.20) hours. These results depict that the quality of soap prepared from these oils fall within the standard specifications. However, the soap prepared from palm kernel oil had overall best quality.